The Argentinean Homosexual Community - Belluci, Mabel (Área Feminismos, Género y Sexualidades del Centro de Investigaciones "María Saleme de Burnichón" de la Facultad de Filosofía y Humanidades, Universidad Nacional de Córdoba, 2021)
The publishing house Final Abierto has just released an expanded and corrected reprint of the book Orgullo: Carlos Jáuregui. Una biografía política, by Mabel Bellucci, originally published by Emecé in 2010. For the magazine Polémicas Feministas we anticipate an excerpt of its first chapter and add photographs from different archives.